Molecular Identification of Cellulolytic Bacteria From Mangrove Sediment at Tin Minning Region In West Bangka - Ardiansyah Kurniawan; Suci Puspita Sari; Euis Asriani; andi kurniawan; abu bakar sambah; asep awaludin prihanto (International Journal of Applied Biology, 2019)
Cellulose as an abundant source of glucose in Indonesia requires acceleration of decomposition utilizing cellulolytic bacteria.  Cellulolytic bacteria can be obtained from the isolation of mangrove organic matter, such as sediments. Muntok Sub-district is one of the regions with the most tin mining in West Bangka Regency also has mangroves in the coastal area. Exploration of cellulolytic bacteria in mangroves with different environmental characteristics encourages researchers to find new bacterial strains that produce cellulase enzymes with new properties. Thirteen isolates were successfully isolated from three locations. Tembelok mangrove sediments produced Seven bacterial isolates, Peltim Mangrove samples produced three isolates and from Sukal Mangrove three isolates were obtained. Seven isolates showed clear zones in the Lugol test and three isolates including were gram-positive bacteria. Molecular test with 16S rRNA analysis showed TBL1 isolate has 85% similar identity of  Vibrio parahaemolyticus strain HY3 and TBL2 isolate has 98% similar identity of Bacillus amyloliquefaciens strain HS8. Bacillus amyloliquefaciens potential to further study as cellulose degrading bacteria for feed ingredients.